The SAGE encyclopedia of research design. 4 - Frey, Bruce B. (Los Angeles, CA : SAGE Publications, Inc., 2022)
This set addresses issues of research design within the experimental sciences broadly speaking, particularly the social/behavioral sciences, neurosciences, and biomedical and life sciences.Entries provide summaries of advantages and disadvantages of often-used designs, along with illustrations using real-life examples.Two topics set this work apart from similar works: a review of important research articles that are seminal in the field and helped to determine the direction, and a review of popular tools (such as software) used to analyze results.Over 500 signed entries organized A-to-Z are available both in print and electronic formats for ease of access and use.Cross-references and suggested readings at the end of each entry, along with an annotated selected bibliography, guide users to additional resources.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Social sciences -- Research -- Encyclopedias; Neurosciences -- Research -- Encyclopedias